Circuitos curtos de comercialização de alimentos: a conquista de territórios para agroecologia no Triângulo Mineiro - Souza, Fernando Cesar de Oliveira (2021)
Faced with the prevailing scenario of a globalized agri-food system that operates towards the subordination of peasant agriculture, new markets are built, like the short food supply chains, as a way to reconnect food producers and consumers. This form of commercialization, as well as agroecology itself, has as a principle, antagonistic logics to those prevailing in the current food regime. In this way, peasants have sought to build by means of short food supply chains an alternative towards the achievement of greater autonomy. In view of the above, the objective of this study was to evaluate and discuss the potential of short agroecological food supply chains, as tools of peasant resistance to the corporate agri-food regime, based on a territorial approach. The methodology of the research is composed of the case study of the experience of agroecological baskets "Sowing Agroforestry", in Uberlândia/MG. Data collection instruments were: documentary analysis, participant observation and semi-structured interviews with actors related to the chain. The analysis of the results pointed to the constitution of a territory, from the social relations based on solidarity, mutual acknowledgment, transparency and learning. The chain demonstrated to be a mechanism, strategy and also product of an agroecological territoriality, ratifying the political potential of agroecology in providing counter-hegemonic paths for the constitution of more ethical, fair and sustainable agri-food systems.